Paediatric reference interval and biological variation trends of thyrotropin (TSH) and free thyroxine (T4) in an Asian population. Issue 8 (22nd April 2015) - Loh, Tze Ping; Sethi, Sunil Kumar; Metz, Michael Patrick
Abstract : Aims: To describe the reference intervals and biological variation data for thyrotropin (TSH) and free thyroxine (FT4) in a mixed Asian population using an indirect sampling approach and to compare them with published reports. Methods: TSH and FT4 of children measured once or twice over a 7-year period (2008–2014) at primary-care and tertiary-care settings were extracted from the laboratory information system. After excluding outliers, age-related reference intervals were derived using the Lambda-Mu-Sigma (LMS) approach, while age-partitioned biological variation data were obtained according to recommendations by Fraser and Harris. Results: Both TSH and FT4 were very high at birth and declined with age. Similarly within-individual and between-individual biological variations were higher for both TSH and FT4 at birth and also declined with age. Our data were broadly similar to previous studies. Significant heterogeneity in study population and methods prohibited direct numerical comparison between this and previously published studies. Conclusions: This study fills two important gaps in our knowledge of paediatric thyroid function by reporting the centile trends (and reference values) in a mixed Asian population, as well as providing age-partitioned biological variation data. The variation in published reference intervals highlights the difficulty in harmonising paediatric thyroid reference intervals or recommending universal clinical cut-offs.